AWARENESS OF STUDENTS OF THE MEDICAL UNIVERSITY ABOUT THE PRE-GRAVIDAR PREPARATION - Елгина, Светлана Ивановна; Кабанова, Светлана Витальевна; Ситникова, Ольга Александровна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Мозес, Кира Борисовна; Черных, Наталья Степановна (Mother and Baby in Kuzbass, 2022)
Pregravidar preparation includes a complex of studies carried out without fail during pregnancy planning. According to the WHO bulletin «Policy of pre-conception training», pre-pregnancy counseling should be carried out for all women of reproductive age at any planned and unscheduled visit to an obstetrician-gynecologist, if the patient does not use reliable contraception, or is not against pregnancy (will not interrupt it). Unfortunately, awareness of the pre-gravidar training of medical university students is insufficient. The solution to this problem can be the active promotion of the need for family planning at the level of educational institutions, women’s consultations, gynecological departments.